Work-hardening effect and strain-rate sensitivity behavior during hot deformation of Ti–5Al–5Mo–5V–1Cr–1Fe alloy. (5th October 2015) - Nan, Yang; Ning, Yongquan; Liang, Houquan; Guo, Hongzhen; Yao, Zekun; Fu, M.W.
Graphical abstract: Highlights: Linear relationship between hardening effect and strain/stress rate was derived. Hardening effect behaves stronger under high Z parameters. Strain-rate sensitivity behavior was illustrated from JMAK kinetics. Strain-rate sensitivity becomes more obvious with lower Z parameters. Abstract: The work-hardening effect and strain-rate sensitivity behavior during hot deformation have been quantitatively investigated in this present paper. Isothermal compression experiment of Ti–5Al–5Mo–5V–1Cr–1Fe titanium alloy has been conducted for verification. Linear relationship between work-hardening rate and true strain/stress has been derived from Kocks–Mecking dislocation relation. The work-hardening effect shows two obvious stages with strain: steady fluctuations and linear decreasing. Obvious work-hardening effect could be demonstrated under lower temperatures and higher strain rates. The work-hardening decrease at linear-decreasing regime becomes more stronger with temperature elevated and rate lowered, reverse-proportional to Zener–Hollomon parameters. Strain-rate sensitivity coefficient for hot deformation was decomposed into three parts from JMAK recrystallization kinetics. The influence of strain rate on DRX evolution has been termed as the major factor determining strain-rate sensitivity. Strain-rate sensitivity coefficients for steady-state deformation ( ɛ  = 0.7) of Ti–5Al–5Mo–5V–1Cr–1Fe alloy have been characterized as a function of deformation parameters and strain-rate sensitivity has been identified more obvious with temperature elevated and rate lowered.